Å reise nordover eller å utfordre det norske: Ailo Gaups Trommereisen og Helene Uris Rydde ut - Sibińska, Maria (Folia Scandinavica Posnaniensia, 2019)
The article elucidates the presence of the Sami undercurrent in Norwegian literature. Proceeding from Elisabeth Oxfeldt’s theoretical work on the post-national and on the Bhabhanian concept third space, two novels are being discussed: Ailo Gaup’s Trommereisen (1988) and Helene Uri’s Rydde ut (2013). Gaup’s works constitute the first samic voice in Norwegian literature, which explicitly verbalizes the despair emanating from the loss of continuity as regards to the self-image and the self-identity of many samic individuals. Uri’s auto-fictional text combines family research with editing and correcting the nation’s biography. Emphasizing the novels employment of the travel north as a driving force behind the plot and as a metaphorical device, the author of the article interprets the novels as an expression of hope to transgress the social reality and re-establish the lost coherence of personal and national history either by means of shamanic knowledge and practice (Trommereisen) or by means of discursive practice (Rydde ut) that liberates the individual from rigid preconceptions regarding identity and cultural belonging.